Cultural Content in Moroccan EFL Textbooks and Cultural Intelligence (CQ) Development - Oumaima Elghazali (Yayasan Visi Intan Permata, 2022)
This study aims at investigating the intercultural adequacy of the cultural content of a Moroccan EFL textbook in developing students’ Cultural Intelligence (CQ). The activities of the textbook were analyzed using the model of Cultural Intelligence (CQ) to identify the adequacy of the intercultural activities in helping students develop their CQ, to detect, assimilate, reason, and act on cultural cues appropriately in situations characterized by cultural diversity. The scale of the same model, the CQ scale, was used to elicit the perspectives of 112 high school teachers regarding the intercultural adequacy of the cultural content in the textbook to compare the results of the two instruments. The results of the analysis of the textbook’s content revealed that the Cognitive CQ is the most present factor of CQ in the textbook activities, but the activities present are not sufficient to develop the students' Cognitive CQ nor the other three CQ factors as illustrated by the CQ model. The elicited perspectives of teachers support the findings of the textbook’s content analysis and suggestions for improvement are enlisted.